STRATEGI PENGEMBANGAN PROGRAM PERTANIAN TANAMAN PANGAN DI DISTRIK SEMANGGA KABUPATEN MERAUKE - Untari Untari (Universitas Musamus, Merauke, Papua, 2011)
The type of research used in this study is descriptive type (survey research) while the analytical method is descriptive. Samples for the population of farmers receiving five priority programs of agricultural sector development is taken by using a random method (sample sampling random), namely population has an equal opportunity to serve as the study sample. To calculate the number of samples using the Slovin formula Umar (1999:161) that uses critical value of 0,1 which is composed of 89 respondents. Data obtained from the investigators will be analized by using analysis of GEP. From the research results can be concluded that the direst did program improved seed (DAPIS) and integrated Crop Management Field School (ICMFS) funded by the state budget funds amounting to Rp. 405.352.700., program agricultural equipment and machinery that have been implemented in the last five years funded the state budget funds amounting to Rp. 27 million, Rp. 18 million to power traser. The program is spread over II groups of farmers who are in 4; program optimization DAK funds funded land, OTSUS and state budget amounting to Rp. 4 million/Ha for planting 340 Ha area and the amount of funds is 1.36 billion, while the program management unit of organic fertilizer derived from the state budget funds a mounting to Rp. 3 million for the development of home composting in three villages.